Method for producing antistatic composite fiber and use thereof

CN122727979APending Publication Date: 2026-09-11GUANGZHOU HUISHENG CLOTHING DESIGN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611115328.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

[0003]但现有抗静电复合纤维在功能填料引入后,往往存在填料在聚合物体系中分散不充分、界面结合力不足的问题,特别是片层状或碳基类导静组分在聚酯基体中易发生团聚,导致其难以形成稳定、连续的导静电作用路径,同时局部界面缺陷还会削弱载荷传递与结构协同性,使所得纤维在后续加工和使用过程中出现功能分布不均、导静作用稳定性不足的问题,由此,如何改善导静功能组分在聚酯体系中的界面适配与分布状态,成为现有技术中需要解决的关键问题之一

Benefits of technology

1、磷硅功能基料进入纤维体系后,并非以简单分散的添加态存在,而是在成形过程中逐步形成相对连续的功能分布区域,由此为导静功能填料提供了更稳定的嵌入与衔接条件,其中,导静功能填料在该环境中不易出现孤立、聚集或传导关联中断的情形,其在纤维截面与近表层区域的配置更趋均衡,随着牵伸及后续成形过程推进,磷硅功能基料对功能相空间状态的维持作用得到延续,使由导静功能填料参与构成的传导关联能够保持较好的连续性,由此,材料在导静相关表征中所呈现出的响应不再主要受局部离散分布影响,而更体现为沿纤维方向和表里区域较为一致的整体状态,加工前后亦保持相对平缓的变化特征。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122727979A_ABST
    Figure CN122727979A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of an antistatic composite fiber, and belongs to the technical field of fiber preparation, and is used for solving the technical problem that the antistatic performance and tensile resistance of the fiber in the prior art need to be further improved; graphene oxide, dopamine hydrochloride and choline lactate are used to prepare a static conduction functional powder, a phosphorus-silicon reaction oligomer, imidazole and a static conduction polyester particle are used to prepare a phosphorus-silicon functional base material, and the static conduction functional powder and the phosphorus-silicon structural unit are further introduced into a polyester system in a stable and cooperative manner to improve the interface organization state and component matching relationship, so that the structural stability, processing adaptability and antistatic function maintaining capacity of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber preparation technology, and specifically to a method for preparing antistatic composite fibers and their applications. Background Technology

[0002] Currently, antistatic composite fibers are typically prepared through surface finishing, blending modification, copolymerization modification, or composite spinning. Among these methods, surface finishing often involves using antistatic agents to form a conductive layer on the fiber or fabric surface; blending modification often involves introducing conductive carbon black, graphite-based materials, metal oxides, or ionic antistatic agents into the polymer matrix; copolymerization modification improves charge dissipation by introducing polar segments into the polymer molecular structure; and composite spinning achieves the conductive properties of fibers through the combination of different functional components. These technologies have been widely applied in the preparation of antistatic materials from synthetic fibers such as polyester.

[0003] However, existing antistatic composite fibers often suffer from insufficient dispersion of fillers in the polymer system and inadequate interfacial bonding after the introduction of functional fillers. In particular, lamellar or carbon-based conductive components are prone to agglomeration in the polyester matrix, making it difficult for them to form a stable and continuous conductive path. At the same time, local interfacial defects can also weaken load transfer and structural synergy, resulting in uneven functional distribution and insufficient stability of conductive effect in subsequent processing and use. Therefore, how to improve the interfacial adaptation and distribution of conductive functional components in the polyester system has become one of the key problems that need to be solved in the existing technology.

[0004] Furthermore, in existing technologies, different functional components are mostly introduced into polymer systems through simple physical blending. There is a lack of stable structural relationships between the components and between the components and the polyester matrix. This leads to the easy migration of functional components, loosening of interfaces, or local structural rearrangement during melt spinning, drawing, and heat treatment, which in turn affects the uniformity of fiber structure and the ability to retain functions. Especially when the system takes into account both mechanical properties and antistatic properties, the two are often difficult to match synergistically. Therefore, how to improve the stable embedding degree and structural synergy of functional components in the continuous polyester phase is still an urgent problem to be solved in the preparation of existing antistatic composite fibers.

[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing antistatic composite fibers and their applications, in order to solve the technical problem that the antistatic properties and tensile strength of fibers in the prior art need to be further improved.

[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing antistatic composite fibers includes the following steps: By weight, weigh 96-99 parts of phosphorus-silicon functional matrix, 0.8-1.2 parts of antistatic functional powder, 0.25-0.35 parts of antioxidant 1010, 0.4-0.6 parts of tris(2,4-di-tert-butylphenyl) phosphite and 0.15-0.25 parts of polydimethylsiloxane and add them to a high-speed mixer for premixing for 10-20 minutes. Then add them to a twin-screw extruder and melt-blend and extrude at 235-250℃. After granulation and drying, add the granules to a melt spinning machine and spin at 252-262℃. Stretch and heat-set to obtain antistatic composite fiber. The phosphorus-silicon functional matrix is ​​prepared by melting and extruding conductive polyester particles, phosphorus-silicon reactive oligomers and catalyst under reactive conditions; the conductive functional powder is prepared by mixing graphene oxide, lactic acid choline, dopamine-like substances and water medium, reacting under alkaline conditions and then separating and drying.

[0008] Furthermore, in the process of preparing antistatic composite fibers, the granulation particle size is 2.5-4.0 mm, the draw ratio is 2.8-3.4 times, the heat setting temperature is 168-182℃, and the heat setting time is 30-45 s.

[0009] Furthermore, the preparation method of the phosphorus-silicon functional matrix is ​​as follows: after uniformly mixing the phosphorus-silicon reactive oligomer and imidazole, it is added together with the conductive polyester particles into a twin-screw extruder, and melt-extruded at 220-230℃ for 8-12 minutes, and then post-processed to obtain the phosphorus-silicon functional matrix.

[0010] Furthermore, the ratio of the phosphorus-silicon reactive oligomer, imidazole, and conductive polyester particles is 21-30g:0.4-0.6g:450-480g. The post-processing includes: cooling and pelletizing the extruded material, controlling the particle size to 2.5-4.0mm, and drying it in a vacuum drying oven at 75-85℃ for 3-5 hours to obtain the phosphorus-silicon functional matrix.

[0011] Furthermore, the preparation method of the conductive polyester particles is as follows: dimethyl terephthalate, sodium isophthalate 5-sulfonate, ethylene glycol, 1,4-cyclohexanediethanol, polyethylene glycol 1000 and zinc acetate dihydrate are added to a reaction vessel and stirred. After stirring evenly, the temperature is raised to 180-190℃ and stirred for 0.8-1.2h, then raised to 200-210℃ and stirred for 1.5-2.5h. Antimony trioxide is then added, and the temperature is further raised to 250-260℃ and stirred for 1.5-2.5h under 30-80Pa conditions. The conductive polyester particles are then obtained after post-treatment.

[0012] Furthermore, the ratio of dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol, 1,4-cyclohexanediethanol, polyethylene glycol 1000, zinc acetate dihydrate, and antimony trioxide is 350-450g:26-34g:150-190mL:65-81g:45-56g:0.3-0.4g:0.16-0.24g. The post-treatment includes: after the reaction, the melt is extruded, cooled, and granulated to control the particle size to 2.5-4.0mm. The resulting granules are then placed in a vacuum drying oven at 115-125℃ and dried for 5-7 hours to obtain conductive polyester granules.

[0013] Furthermore, the preparation method of the phosphorus-silicon reactive oligomer is as follows: 3-(2,3-epoxypropoxy)propyltrimethoxysilane, diethyl phosphite and imidazole are added to a reaction vessel and stirred. After stirring evenly, the temperature is raised to 92-105℃ and stirred for 3.5-5 hours. Then the temperature is lowered to 35-45℃ and anhydrous ethanol is added. Then the mixture is added and the temperature is raised to 48-55℃ and stirred for 4-6 hours. The phosphorus-silicon reactive oligomer is obtained after post-treatment.

[0014] Furthermore, the ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, diethyl phosphite, imidazole, anhydrous ethanol, and the mixture is 60-72 mL:14-18 mL:0.5-0.7 g:50-65 mL:14-18 mL, wherein the mixture is obtained by mixing deionized water and anhydrous ethanol at a ratio of 14-18 mL:0.5-0.7 mL. The post-treatment includes: removing volatile components under reduced pressure after the reaction, placing the obtained material under reduced pressure at 55-65°C for 0.5-1.5 h, and then allowing it to stand at 75-85°C for 1.5-2.5 h to obtain the phosphorus-silicon reactive oligomer.

[0015] Furthermore, the preparation method of the conductive powder is as follows: 0.2-0.4wt% tris(hydroxymethyl)aminomethane aqueous solution is added to the reaction vessel, the pH is adjusted to 8.3-8.7 using 1.0wt% hydrochloric acid aqueous solution, then graphene oxide is added for dispersion, and after uniform dispersion, dopamine hydrochloride and lactic choline are added. The mixture is kept at 25-35℃ and stirred for 6-10 hours, and then post-processed to obtain the conductive powder.

[0016] Furthermore, the ratio of the 0.2-0.4wt% tris(hydroxymethyl)aminomethane aqueous solution, graphene oxide, dopamine hydrochloride, and lactic choline is 900-1100mL:9-12g:18-24g:13-18mL. The post-treatment includes: after the reaction is completed, filtering and collecting the filter cake, washing the filter cake sequentially with deionized water and anhydrous ethanol, drying the filter cake in a vacuum drying oven at 45-55℃ for 10-14h, pulverizing and passing it through an 80-120 mesh sieve to obtain the static-conducting functional powder.

[0017] The present invention also discloses an application of an antistatic composite fiber, which is used in the preparation of work clothes and cleanroom antistatic clothing.

[0018] The present invention has the following beneficial effects: 1. After the phosphorus-silicon functional matrix enters the fiber system, it does not exist in a simple dispersed additive state, but gradually forms a relatively continuous functional distribution area during the forming process. This provides more stable embedding and connection conditions for the conductive and static functional filler. In this environment, the conductive and static functional filler is less likely to be isolated, aggregated, or have its conductive correlation interrupted. Its configuration in the fiber cross section and near-surface area is more balanced. As the drawing and subsequent forming processes progress, the phosphorus-silicon functional matrix continues to maintain the spatial state of the functional phase, so that the conductive correlation formed by the conductive and static functional filler can maintain good continuity. As a result, the response of the material in the conductive and static correlation characterization is no longer mainly affected by local discrete distribution, but is more reflected as a relatively consistent overall state along the fiber direction and in the inner and outer regions, and maintains a relatively gentle change characteristic before and after processing.

[0019] 2. Under dynamic contact and repeated friction conditions, the role of the electrostatic conductive filler is not limited to the static conduction nodes themselves. In the interface environment constructed by the phosphosilicone functional matrix, it is easier to maintain dispersion and connectivity. As a result, the charge formed on the fiber surface is no longer concentrated in a few local areas. At the same time, the phosphosilicone functional matrix plays a role in sorting out the connection between the surface and internal functional phases, making the charge migration path associated with the electrostatic conductive filler smoother. The process of charge generation, transfer and release shows good continuity. This is not an isolated change in a single link, but a coordinated unfolding of the entire electrostatic response process. Correspondingly, the material is more likely to show a stable, continuous and less fluctuating response state in the antistatic behavior related characterization, reflecting the dynamic consistency of the new material system in actual use.

[0020] 3. When the phosphosilica functional matrix and the conductive and static-conducting functional filler are introduced into the system together, they do not appear as separate heterogeneous rigid components. The phosphosilica functional matrix has a significant regulating effect on the interface state around the conductive and static-conducting functional filler, making the phase transition formed after the functional filler enters the fiber relatively smooth, and mitigating the tendency of defect initiation caused by local abrupt changes. The conductive and static-conducting functional filler maintains its functional configuration in this relatively stable enclosed environment, and does not further amplify into structural disturbance due to interface mismatch. As a result, during stretching, winding, and subsequent stress deformation, the synergistic relationship between the functional phases inside the system can remain relatively stable, and local stress is less likely to evolve into obvious structural damage. Correspondingly, while completing the configuration of functional components, the overall structural state of the material still maintains the coordination and integrity to adapt to the requirements of subsequent processing and use. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a SEM image of the static-conducting functional powder prepared in Example 6 of the present invention. Detailed Implementation

[0023] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] In this application, the graphene oxide used is sheet-like graphene oxide powder with 1-2 layers, a sheet diameter of 2.0-3.0 μm, a thickness of 0.9-1.2 nm, and an oxygen content of 30-33 wt%; the polyethylene glycol 1000 used is polyethylene glycol with a number average molecular weight of 990-1010, a hydroxyl value of 111-114 mgKOH / g, and a moisture content of no more than 0.1 wt%; the polydimethylsiloxane used is a dimethylsiloxane homopolymer with a kinematic viscosity of 105-115 mPa·s at 25°C, a number average molecular weight of 4500-5500, and a volatile content of no more than 0.3 wt%.

[0025] Example 1 This embodiment provides a method for preparing a phosphorus-silicon functional matrix, including the following steps: Step ①: Preparation of static-conducting polyester particles Weigh out 350.0g of dimethyl terephthalate, 26.0g of sodium 5-sulfonate dimethyl isophthalate, 150.0mL of ethylene glycol, 65.0g of 1,4-cyclohexanediethanol, 45.0g of polyethylene glycol 1000 and 0.3g of zinc acetate dihydrate and add them to the reaction vessel. Stir until uniform, then heat to 180℃ and stir for 0.8h. Then heat to 200℃ and stir for 1.5h. Add 0.2g of antimony trioxide, continue to heat to 250℃ and stir for 1.5h under 30Pa. After the reaction is complete, extrude the melt, cool and granulate, control the particle size to 2.5mm, and then dry the obtained granules in a vacuum drying oven at 115℃ for 5h to obtain conductive polyester granules.

[0026] The reaction principle for preparing conductive polyester particles is as follows: Dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol, 1,4-cyclohexanediethanol, and polyethylene glycol 1000 first undergo transesterification under catalytic conditions, with methoxy groups gradually being replaced by hydroxyl groups to form corresponding low-polyester intermediates. As the reaction temperature increases and antimony trioxide is added, the system further undergoes a polycondensation reaction, with the molecular chain continuously growing and small molecule byproducts being continuously removed, resulting in a gradual increase in the molecular weight of the polyester. Sodium 5-sulfonate dimethyl isophthalate, as a comonomer containing sodium sulfonate groups, enters the polyester backbone, while polyethylene glycol 1000 is introduced into the molecular structure in the form of chain segments, ultimately yielding copolyester particles containing aromatic ester structures, alicyclic diol structures, polyether segments, and sodium sulfonate groups.

[0027] Step 2: Preparation of phosphorus-silicon reactive oligomers Weigh out 14.0 mL of deionized water and 0.5 mL of acetic acid and mix them to obtain a mixture; Weigh out 60.0 mL of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 14.0 mL of diethyl phosphite, and 0.5 g of imidazole and add them to a reaction vessel. Stir until homogeneous, then heat to 92 °C and stir for 3.5 h. Then cool to 35 °C and add 50.0 mL of anhydrous ethanol, followed by 14.0 mL of the mixture. Continue heating to 48 °C and stirring for 4 h. After the reaction is complete, remove the volatile components under reduced pressure. Place the resulting material under reduced pressure at 55 °C for 0.5 h, and then let it stand at 75 °C for 1.5 h to obtain the phosphorus-silicon reactive oligomer.

[0028] The reaction principle for preparing phosphorus-silicon reactive oligomers is as follows: The 3-(2,3-epoxypropoxy)propyltrimethoxysilane molecule contains both epoxy and trimethoxysilane groups. In the presence of imidazole, diethyl phosphite first undergoes a ring-opening addition reaction with the epoxy group, linking the phosphorus-containing structure to the organosilicon molecule. Subsequently, after the addition of an aqueous acidic mixture, the trimethoxysilane group gradually hydrolyzes to generate silanol groups. The silanols then undergo further condensation to form a Si-O-Si bonded oligomeric siloxane structure. In this process, the organophosphorus-containing structure and the siloxane structure are combined into the same oligomer system. The resulting product is essentially a reactive oligomer containing both organophosphorus and siloxane oligomer structures.

[0029] Step 3: Preparation of phosphorus-silicon functional matrix Weigh out 21.0g of phosphorus-silicon reactive oligomer and 0.4g of imidazole, mix them evenly, and add them together with 450.0g of conductive polyester granules into a twin-screw extruder. Melt extrusion reaction is carried out at 220℃ for 8min. After extrusion, the material is cooled, granulated, and the particle size is controlled to be 2.5mm. It is then placed in a vacuum drying oven at 75℃ for 3h to obtain phosphorus-silicon functional matrix.

[0030] The reaction principle for preparing phosphorus-silicon functional materials is as follows: Under melt extrusion conditions, the conductive polyester particles are transformed into a continuous polyester melt. The phosphorus-silicon reactive oligomers are fully contacted and dispersed in the system under the action of imidazole. The residual active groups in the oligomers can react with the end groups of the polyester molecular chains. At the same time, its siloxane oligomer structure and phosphorus-containing organic structure can exist stably in the polyester matrix, thus forming a reactive composite system with polyester as the continuous phase and phosphorus-silicon structural units introduced into it. After melt extrusion, cooling and pelletizing, the resulting particles are polymer base materials formed by the combination of phosphorus-silicon structural components and polyester matrix. Its essence is modified polyester particles after the introduction of phosphorus-silicon components.

[0031] The mechanism of action of phosphorus-silicon functional matrix materials in antistatic composite fibers is as follows: The structural basis of phosphosilicon functional matrix materials originates from phosphorus-containing organic units, siloxane segments, and their residual active structures provided by phosphosilicon reactive oligomers. Together with a conductive polyester continuous phase as the supporting skeleton, they form a composite system. The phosphorus-containing structure helps to enhance the polarity characteristics and functional component constraint ability of the system, while the siloxane segments endow the local interface with good flexibility and adaptability. After entering the polyester matrix, both can change the existence mode and spatial distribution of functional units in the continuous phase. Although imidazole does not play a role as the final main component, it affects the sufficiency and fixation of the binding between the phosphosilicon structural units and the polyester matrix. The resulting phosphosilicon functional matrix material is no longer a simple polyester particle, but a modified polyester matrix material with phosphosilicon structure embedding characteristics. Its internal interface organization, functional phase stability, and subsequent component matching ability are all reshaped, further affecting the uniformity, processing stability, and functional retention of the matrix material.

[0032] Example 2 This embodiment provides a method for preparing a phosphorus-silicon functional matrix, including the following steps: Step ①: Preparation of static-conducting polyester particles Weigh out 450.0g of dimethyl terephthalate, 34.0g of sodium 5-sulfonate dimethyl isophthalate, 190.0mL of ethylene glycol, 81.0g of 1,4-cyclohexanediethanol, 56.0g of polyethylene glycol 1000 and 0.4g of zinc acetate dihydrate and add them to the reaction vessel. Stir until uniform, then heat to 190℃ and stir for 1.2h. Then heat to 210℃ and stir for 2.5h. Add 0.2g of antimony trioxide and continue to heat to 260℃ and stir for 2.5h under 80Pa. After the reaction is complete, extrude the melt, cool and granulate, control the particle size to 4.0mm, and then dry the obtained granules in a vacuum drying oven at 125℃ for 7h to obtain conductive polyester granules.

[0033] Step 2: Preparation of phosphorus-silicon reactive oligomers Weigh out 18.0 mL of deionized water and 0.7 mL of acetic acid and mix them to obtain a mixture; Weigh out 72.0 mL of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 18.0 mL of diethyl phosphite, and 0.7 g of imidazole and add them to a reaction vessel. Stir until homogeneous, then heat to 105 °C and stir for 5.0 h. Then cool to 45 °C and add 65.0 mL of anhydrous ethanol, followed by 18.0 mL of the mixture. Continue heating to 55 °C and stirring for 6 h. After the reaction is complete, remove the volatile components under reduced pressure. Place the resulting material under reduced pressure at 65 °C for 1.5 h, and then let it stand at 85 °C for 2.5 h to obtain the phosphorus-silicon reactive oligomer.

[0034] Step 3: Preparation of phosphorus-silicon functional matrix Weigh out 30.0g of phosphorus-silicon reactive oligomer and 0.6g of imidazole, mix them evenly, and add them together with 480.0g of conductive polyester granules into a twin-screw extruder. Melt extrusion reaction is carried out at 230℃ for 12min. After extrusion, the material is cooled, granulated, and the particle size is controlled to be 4.0mm. It is then placed in a vacuum drying oven at 85℃ for 5h to obtain phosphorus-silicon functional matrix.

[0035] Example 3 This embodiment provides a method for preparing a phosphorus-silicon functional matrix, including the following steps: Step ①: Preparation of static-conducting polyester particles Weigh out 400.0g of dimethyl terephthalate, 30.0g of sodium 5-sulfonate dimethyl isophthalate, 170.0mL of ethylene glycol, 73.0g of 1,4-cyclohexanediethanol, 50.5g of polyethylene glycol 1000, and 0.4g of zinc acetate dihydrate and add them to the reaction vessel. Stir until homogeneous, then heat to 185℃ and stir for 1.0h. Then heat to 205℃ and stir for 2.0h. Add 0.2g of antimony trioxide, continue heating to 255℃ and stir for 2.0h at 55Pa. After the reaction is complete, extrude the melt, cool and granulate, controlling the particle size to 3.3mm. Then place the obtained granules in a vacuum drying oven at 120℃ and dry for 6h to obtain conductive polyester granules.

[0036] Step 2: Preparation of phosphorus-silicon reactive oligomers Weigh out 16.0 mL of deionized water and 0.6 mL of acetic acid and mix them to obtain a mixed solution; Weigh out 66.0 mL of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 16.0 mL of diethyl phosphite, and 0.6 g of imidazole and add them to a reaction vessel. Stir until homogeneous, then heat to 99 °C and stir for 4.3 h. Then cool to 40 °C and add 57.5 mL of anhydrous ethanol, followed by 16.0 mL of the mixture. Continue heating to 52 °C and stirring for 5 h. After the reaction is complete, remove the volatile components under reduced pressure. Place the resulting material under reduced pressure at 60 °C for 1.0 h, and then let it stand at 80 °C for 2.0 h to obtain the phosphorus-silicon reactive oligomer.

[0037] Step 3: Preparation of phosphorus-silicon functional matrix Weigh out 25.5g of phosphorus-silicon reactive oligomer and 0.5g of imidazole, mix them evenly, and add them together with 465.0g of conductive polyester granules into a twin-screw extruder. Melt extrusion reaction is carried out at 225℃ for 10min. After extrusion, the material is cooled, granulated, and the particle size is controlled to be 3.3mm. It is then placed in a vacuum drying oven at 80℃ for 4h to obtain phosphorus-silicon functional matrix.

[0038] Example 4 This embodiment provides a method for preparing antistatic composite fibers, including the following steps: Step 1: Preparation of the conductive and static-relieving powder Weigh 900.0 mL of 0.2 wt% tris(hydroxymethyl)aminomethane aqueous solution and add it to the reaction vessel. Adjust the pH to 8.3 using 1.0 wt% hydrochloric acid aqueous solution. Then add 9.0 g of graphene oxide for dispersion. After uniform dispersion, add 18.0 g of dopamine hydrochloride and 13.0 mL of lactic choline. Keep the mixture at 25 °C and stir for 6 h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake with deionized water and anhydrous ethanol in sequence. Then place the filter cake in a vacuum drying oven at 45 °C and dry for 10 h. Crush and pass through an 80-mesh sieve to obtain the static-conducting functional powder.

[0039] The reaction principle for preparing the conductive and static-relieving functional powder is as follows: The surface of graphene oxide contains oxygen-containing functional groups such as hydroxyl, carboxyl, and epoxy groups. Under weakly alkaline conditions, dopamine hydrochloride undergoes oxidative polymerization, gradually forming polydopamine, which is deposited on the surface of graphene oxide. This deposition process forms an organic coating structure on the surface of the graphene oxide sheets, and the surface composition of the composite powder changes from the original oxygen-containing carbon material surface to an interface structure where graphene oxide and polydopamine coexist. After the addition of lactic choline, it interacts with the oxygen-containing groups and polydopamine structure in the system and remains on the surface or interlayer region of the composite powder. After separation, washing, and drying, a conductive functional powder composed of graphene oxide, polydopamine, and lactic choline is finally obtained.

[0040] The mechanism of action of the conductive powder in antistatic composite fibers is as follows: The structural basis of the conductive and static-dissipating functional powder originates from the surface / interlayer synergistic structure composed of graphene oxide sheets, a polydopamine coating layer formed by dopamine polymerization, and lactic acid choline. Among them, graphene oxide provides a conductive carbon-based framework and sheet carrier, determining the basic conductive and static-dissipating properties of the powder; the polydopamine coating layer endows the powder surface with more actionable sites and interfacial buffering characteristics, transforming its surface state from a single oxygen-containing carbon material surface to an organic-inorganic composite interface; lactic acid choline further participates in the regulation of the surface and interlayer microenvironment, helping to improve the interfacial affinity and structural stability of the functional powder. The resulting conductive and static-dissipating functional powder is no longer a simple graphene oxide powder, but a functional filler with composite interfacial characteristics. Its surface chemical environment, interparticle interaction mode, and dispersion and adaptation ability in subsequent systems are all changed, further affecting the continuity of its conductive and static-dissipating effect, interfacial bonding state, and functional retention basis.

[0041] Step 2: Preparation of antistatic composite fibers By weight, 96.0 parts of the phosphorus-silicon functional matrix prepared in step 1, 0.8 parts of the antistatic functional powder, 0.3 parts of antioxidant 1010, 0.4 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.2 parts of polydimethylsiloxane were weighed and added to a high-speed mixer for premixing for 10 min. Then, the mixture was added to a twin-screw extruder and melt-blended and extruded at 235°C. The mixture was then granulated to a particle size of 2.5 mm, dried, and the granules were added to a melt spinning machine. The mixture was then spun at 252°C with a draw of 2.8 times and heat-set at 168°C for 30 s to obtain an antistatic composite fiber with a diameter of 18 μm.

[0042] The reaction principle for preparing antistatic composite fibers is as follows: Phosphorus-silicon functional matrix forms polyester melt under heating conditions. Antistatic functional powder is dispersed into the polymer system during melt blending. Antioxidant 1010 and tris(2,4-di-tert-butylphenyl) phosphite are used to inhibit the thermal oxidation reaction during melt processing. Polydimethylsiloxane participates in the melt processing. After blending and extrusion, the components form a uniformly composed composite granule. In the subsequent melt spinning process, the composite granule is melted again and formed into a continuous monofilament structure through spinning, drawing and heat setting. The main processes in this process are the flow and shaping of the polymer melt, the retention of dispersed components, and the orientation and solidification of molecular chains, ultimately resulting in antistatic composite fibers.

[0043] Example 5 This embodiment provides a method for preparing antistatic composite fibers, including the following steps: Step 1: Preparation of the conductive and static-relieving powder Weigh 1100.0 mL of 0.4 wt% tris(hydroxymethyl)aminomethane aqueous solution and add it to the reaction vessel. Adjust the pH to 8.7 using 1.0 wt% hydrochloric acid aqueous solution. Then add 12.0 g of graphene oxide for dispersion. After uniform dispersion, add 24.0 g of dopamine hydrochloride and 18.0 mL of lactic choline. Keep the mixture at 35 °C and stir for 10 h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake with deionized water and anhydrous ethanol in sequence. Then place the filter cake in a vacuum drying oven at 55 °C and dry for 14 h. Crush and pass through a 120 mesh sieve to obtain the static-conducting functional powder.

[0044] Step 2: Preparation of antistatic composite fibers By weight, 99.0 parts of the phosphorus-silicon functional matrix prepared in Example 2, 1.2 parts of the antistatic functional powder, 0.3 parts of antioxidant 1010, 0.6 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.2 parts of polydimethylsiloxane were weighed and added to a high-speed mixer for premixing for 20 min. Then, the mixture was added to a twin-screw extruder and melt-blended and extruded at 250°C. The mixture was then granulated to a particle size of 4.0 mm, dried, and the granules were added to a melt spinning machine. The mixture was then spun at 262°C with a draw of 3.4 times and heat-set at 182°C for 45 s to obtain an antistatic composite fiber with a diameter of 18 μm.

[0045] Example 6 This embodiment provides a method for preparing antistatic composite fibers, including the following steps: Step 1: Preparation of the conductive and static-relieving powder Weigh 1000.0 mL of 0.3 wt% tris(hydroxymethyl)aminomethane aqueous solution and add it to the reaction vessel. Adjust the pH to 8.5 using 1.0 wt% hydrochloric acid aqueous solution. Then add 10.5 g of graphene oxide for dispersion. After uniform dispersion, add 21.0 g of dopamine hydrochloride and 15.5 mL of lactic choline. Keep the mixture at 30 °C and stir for 8 h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake with deionized water and anhydrous ethanol in sequence. Then place the filter cake in a vacuum drying oven at 50 °C and dry for 12 h. Crush and pass through a 100-mesh sieve to obtain the static-conducting functional powder.

[0046] Step 2: Preparation of antistatic composite fibers By weight, 97.5 parts of the phosphorus-silicon functional matrix prepared in Example 3, 1.0 part of the antistatic functional powder, 0.3 parts of antioxidant 1010, 0.5 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.2 parts of polydimethylsiloxane were weighed and added to a high-speed mixer for premixing for 15 min. Then, the mixture was added to a twin-screw extruder and melt-blended and extruded at 243°C. The mixture was then granulated to a particle size of 3.3 mm, dried, and the granules were added to a melt spinning machine. The mixture was then spun at 257°C with a draw of 3.1 times and heat-set at 175°C for 38 s to obtain an antistatic composite fiber with a diameter of 18 μm.

[0047] Comparative Example 1 The difference between this comparative example and Example 6 is that in step two, steps ② and ③ of the phosphorus-silicon functional matrix are omitted during the preparation process, and the conductive polyester particles prepared in step ① are used to replace the phosphorus-silicon functional matrix in an equal amount.

[0048] Comparative Example 2 The difference between this comparative example and Example 6 is that, in step two, the addition of imidazole was omitted in step ③ of the preparation process of the phosphorus-silicon functional base material.

[0049] Comparative Example 3 The difference between this comparative example and Example 6 is that in step one, the addition of dopamine hydrochloride and lactic acid choline is omitted.

[0050] Performance testing: The test samples used for performance testing are divided into two categories: fabric samples and filament samples. The surface resistivity, triboelectric voltage and electrostatic voltage half-life are obtained from fabric samples made of antistatic composite fibers obtained in Examples 4-6 and Comparative Examples 1-3. The breaking strength and breaking elongation are obtained from filament samples cut from the middle of the corresponding spools of antistatic composite fibers obtained in Examples 4-6 and Comparative Examples 1-3. The fabric samples were all made from undyed, unfinished plain-weave woven fabrics. Both warp and weft yarns were made from the prepared antistatic composite fiber filaments. No other conductive fibers or finishing antistatic agents were added during processing. To ensure the comparability of test results across groups, all fabric samples were prepared using the same weaving process, with a width controlled at 150±5cm, warp density controlled at 420±10 threads / 10cm, weft density controlled at 300±10 threads / 10cm, and areal density controlled at 80±5g / m². 2 The thickness is controlled at 0.12±0.02mm; during the electrostatic performance test, all samples are cut along the same sampling direction, and the cutting size of a single sample is in accordance with the requirements of the corresponding test standard; when cutting the sample, avoid the fabric edge, crease, damage, oil stains and other visible defects, and the test area is not less than 10mm away from the fabric edge. All filament samples were taken from the middle of the packaged yarn obtained under the same forming process conditions. Before testing, obvious fuzzy, contaminated, and mechanically damaged yarn segments were removed. Unless otherwise specified, before electrostatic performance testing, all fabric samples were conditioned for 24 hours at 23±2℃ and 40±4% relative humidity; before mechanical performance testing, all filament samples were placed for 24 hours at 20±2℃ and 65±5% relative humidity. Three sets of parallel samples were set up for each item. For fabric items, three independent samples were used in each set, and for filament items, 20 filaments were tested in each set. The results were taken as the arithmetic mean.

[0051] Surface resistivity was measured in accordance with GB / T 12703.4-2010 "Evaluation of electrostatic properties of textiles - Part 4: Resistivity", and the test results are expressed as surface resistivity in Ω. The specific testing method is as follows: The surface resistivity tester with a ring electrode is used for measurement. The test voltage is set to 100V. After 60s of power-on, the stable value is read. For each fabric sample, the test position is changed 5 times in the effective area not less than 10mm from the edge of the fabric. The average value is taken as the result of the sample. The average value of 3 parallel samples is taken as the final result.

[0052] The triboelectric voltage was determined in accordance with GB / T 12703.5-2020 "Test methods for electrostatic properties of textiles - Part 5: Rotational mechanical friction method", and the test result is expressed as triboelectric voltage in V. The specific testing method is as follows: A rotating mechanical triboelectric electrostatic tester is used, and the sample and friction material are clamped according to the standard specifications for testing. A new sample or non-friction area is replaced for each test, and the sample is re-humidified according to the standard requirements after each test before the next test is conducted. Each sample is measured independently 3 times, and the average value is taken as the result of that sample. The average value of 3 parallel samples is then taken as the final result.

[0053] The electrostatic half-life was determined in accordance with GB / T 12703.1-2021 "Textiles - Test methods for electrostatic properties - Part 1: Corona charging method". The test results are expressed as electrostatic half-life in seconds. The specific test method is as follows: A corona charging electrostatic tester is used to charge the sample according to the standard and record the static voltage decay curve. The time corresponding to the static voltage decaying to 50% of the initial peak value is taken as the static voltage half-life. Each sample is measured independently 3 times, and the average value is taken as the result of that sample. The average value of 3 parallel samples is then taken as the final result.

[0054] The tensile strength was determined in accordance with GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments", and the test results are expressed as tensile strength, with the unit being cN / dtex. The specific testing method is as follows: The test is conducted using an electronic tensile testing machine with constant speed elongation. The test object is a filament sample extracted from the filament package. The spacing length is set to 500 mm, and the tensile speed is set to 500 mm / min. The linear density is calculated by converting the actual linear density of the corresponding filament sample. Each group tests 20 filaments, and the arithmetic mean is taken as the final result.

[0055] The elongation at break was determined according to GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments". The test result is expressed as elongation at break, in percentage (%). The specific testing method is as follows: the testing instruments, sample selection, spacing length and tensile speed are the same as those for the breaking strength test. The breaking elongation is calculated based on the elongation value of the filament when it is stretched to break. Each group tests 20 filaments and takes the arithmetic mean as the final result.

[0056] Table 1 - Performance Test Data for Each Sample Surface resistivity / Ω 4.36 4.24 4.11 6.87 5.71 6.28 Triboelectric voltage / V 21.4 20.8 20.1 35.6 29.8 32.4 Static voltage half-life / s 6.4×109 6.2×109 6.1×109 9.7×109 8.3×109 9.0×109 Fracture strength / cN·dtex-1 1360 1372 1385 1218 1276 1249 Elongation at break / % 2.1 2.2 2.3 1.6 1.8 1.7 Data Analysis: A comparative analysis of the data in Table 1 reveals that the tensile strength of the antistatic composite fiber prepared in this invention is 1385 cN·dtex. -1 The fabric exhibits a breaking elongation of 2.3%, a surface resistivity of 4.11Ω, a triboelectric voltage of 20.1V, and a static voltage half-life of 6.1×10⁻⁶. 9 s, all data are better than the comparative example, indicating: In Comparative Example 1, the phosphorus-silicon related structures failed to be pre-embedded and interface-built in the polyester carrier, resulting in a lack of stable support environment for the subsequent conductive and antistatic functional powders. This made it easier for local aggregation and dispersion to occur during melt blending and spinning, making it difficult to form a continuous and balanced conductive relationship. At the same time, insufficient phase transition increased local structural abrupt changes, making it easier to induce defect accumulation under thermal processing and stress conditions, which in turn caused a decrease in the uniformity of conductive and antistatic response, the persistence of antistatic properties, and the overall structural stability.

[0057] In Comparative Example 2, when the reaction coupling is insufficient during the formation of the functional matrix, the bonding state between the phosphorus silicon component and the polyester carrier is not stable enough. The functional phase and interface fixation relationship that should have been established is weakened, resulting in a decrease in the system's ability to constrain, disperse, and regulate the interface of the electrostatic functional powder. Consequently, the spatial arrangement of the functional filler is more prone to fluctuation during the forming process, and the local conduction correlation is difficult to maintain continuity. Furthermore, under the effects of thermal history and stretching, the phase mismatch is further amplified, leading to a decrease in electrostatic response stability and overall structural coordination.

[0058] In Comparative Example 3, when an effective interface conditioning layer is not formed on the surface of the conductive functional powder, its dispersion, embedding, and interfacial bonding in the composite system are restricted, making it difficult to establish a sufficient and uniform correlation with the surrounding functional phases. As a result, the filler is more prone to agglomeration or local enrichment during premixing, blending, and spinning, and the charge migration path tends to be discrete and discontinuous. At the same time, the interface mismatch will also exacerbate local stress concentration, weaken the coordination between functional response and structural retention, and ultimately lead to an overall decline in composite performance.

[0059] Ultimately, it is demonstrated that the performance changes of this system do not depend on the independent action of a single component, but are intrinsically related to the material configuration, interfacial structure, and structural maintenance during the forming process. When any of the aforementioned aspects are adjusted, the embedding, distribution, and connection relationships of functional components in the continuous polyester phase change accordingly, and the stability of the microenvironment around the conductive filler and the continuity of the conductive connection are also affected. At the same time, changes in the interphase transition state will further affect the structural rearrangement during melt flow, spinning drawing, and heat setting processes, causing a shift in the matching relationship between functional response and fiber structure. Thus, the results presented by this scheme further reflect the systematic construction effect under multi-step connection.

[0060] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

[0061] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0062] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing antistatic composite fibers, characterized in that, Includes the following steps: By weight, weigh 96-99 parts of phosphorus-silicon functional matrix, 0.8-1.2 parts of antistatic functional powder, 0.25-0.35 parts of antioxidant 1010, 0.4-0.6 parts of tris(2,4-di-tert-butylphenyl) phosphite and 0.15-0.25 parts of polydimethylsiloxane and add them to a high-speed mixer for premixing for 10-20 minutes. Then add them to a twin-screw extruder and melt-blend and extrude at 235-250℃. After granulation and drying, add the granules to a melt spinning machine and spin at 252-262℃. Stretch and heat-set to obtain antistatic composite fiber. The phosphorus-silicon functional matrix is ​​prepared by melting and extruding conductive polyester particles, phosphorus-silicon reactive oligomers and catalyst under reactive conditions; the conductive functional powder is prepared by mixing graphene oxide, lactic acid choline, dopamine-like substances and water medium, reacting under alkaline conditions and then separating and drying.

2. According to claim 1, in the process of preparing antistatic composite fiber, the granulation particle size is 2.5-4.0 mm, the draw ratio is 2.8-3.4 times, the heat setting temperature is 168-182℃, and the heat setting time is 30-45 s.

3. The method for preparing an antistatic composite fiber according to claim 1, characterized in that, The preparation method of the phosphorus-silicon functional matrix is ​​as follows: after uniformly mixing the phosphorus-silicon reactive oligomer and imidazole, it is added together with the static-conducting polyester particles into a twin-screw extruder and melt-extruded at 220-230℃ for 8-12 minutes. The phosphorus-silicon functional matrix is ​​then obtained after post-treatment. The ratio of the phosphorus-silicon reactive oligomer, imidazole and static-conducting polyester particles is 21-30g:0.4-0.6g:450-480g.

4. The method for preparing an antistatic composite fiber according to claim 3, characterized in that, The method for preparing the conductive polyester particles is as follows: Dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol, 1,4-cyclohexanediethanol, polyethylene glycol 1000 and zinc acetate dihydrate are added to a reaction vessel and stirred. After stirring evenly, the temperature is raised to 180-190℃ and stirred for 0.8-1.2h, then raised to 200-210℃ and stirred for 1.5-2.5h. Antimony trioxide is then added, and the temperature is further raised to 250-260℃ and stirred for 1.5-2.5h under 30-80Pa conditions. The conductive polyester particles are then obtained after post-treatment.

5. The method for preparing an antistatic composite fiber according to claim 4, characterized in that, The ratio of dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol, 1,4-cyclohexanediethanol, polyethylene glycol 1000, zinc acetate dihydrate, and antimony trioxide is 350-450g:26-34g:150-190mL:65-81g:45-56g:0.3-0.4g:0.16-0.24g.

6. The method for preparing an antistatic composite fiber according to claim 3, characterized in that, The preparation method of the phosphorus-silicon reactive oligomer is as follows: 3-(2,3-epoxypropoxy)propyltrimethoxysilane, diethyl phosphite and imidazole are added to a reaction vessel and stirred. After stirring evenly, the temperature is raised to 92-105℃ and stirred for 3.5-5 hours. Then the temperature is lowered to 35-45℃ and anhydrous ethanol is added. Then the mixture is added and the temperature is raised to 48-55℃ and stirred for 4-6 hours. The phosphorus-silicon reactive oligomer is obtained after post-treatment.

7. The method for preparing an antistatic composite fiber according to claim 6, characterized in that, The ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, diethyl phosphite, imidazole, anhydrous ethanol, and the mixture is 60-72 mL: 14-18 mL: 0.5-0.7 g: 50-65 mL: 14-18 mL, wherein the mixture is obtained by mixing deionized water and anhydrous ethanol in a ratio of 14-18 mL: 0.5-0.7 mL.

8. The method for preparing an antistatic composite fiber according to claim 1, characterized in that, The preparation method of the conductive and static-relieving functional powder is as follows: 0.2-0.4wt% tris(hydroxymethyl)aminomethane aqueous solution is added to the reaction vessel, and the pH is adjusted to 8.3-8.7 using 1.0wt% hydrochloric acid aqueous solution. Then, graphene oxide is added for dispersion. After uniform dispersion, dopamine hydrochloride and lactic choline are added. The mixture is kept at 25-35℃ and stirred for 6-10 hours. The conductive and static-relieving functional powder is obtained after post-treatment.

9. The method for preparing an antistatic composite fiber according to claim 8, characterized in that, The ratio of the 0.2-0.4wt% tris(hydroxymethyl)aminomethane aqueous solution, graphene oxide, dopamine hydrochloride, and lactic choline is 900-1100mL:9-12g:18-24g:13-18mL.

10. An application of an antistatic composite fiber, characterized in that, The composite antistatic fiber prepared by the method of any one of claims 1-9 is used in the preparation of work clothes and cleanroom antistatic clothing.